The use of blockchain technology in medicine. Literature review and future perspectives - Młodawski, Jakub; Mlodawska, Marta; Sikorski, Marek; Swiercz, Grzegorz (Medical Studies/Studia Medyczne, 2023)
Blockchain technology, the backbone of cryptocurrencies such as Bitcoin, is a rapidly growing field with a wide range of potential applications, including in the medical field. The ability to securely and transparently store and share data makes it a promising technology for various applications in healthcare. In this narrative review, we will explore the ways in which blockchain technology is being used in medicine, the potential benefits and challenges of using this technology, and the future directions for research in this area.